Vibration Diagnostics for Predicting Pump Failures: Diagnostik Getaran untuk Memprediksi Kegagalan Pompa - Barafi, Keigant Abdullah; Fahruddin, A’rasy (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the predictive potential of specific vibration patterns in assessing the structural integrity of centrifugal pumps, vital for industrial fluid transport. Despite their importance, these pumps often encounter performance issues attributed to vibration-related damage such as cavitation and corrosion. Addressing this gap, we employ advanced vibration analysis techniques to identify distinct signatures indicative of cavitation and corrosion progression. Our research aims to provide an early detection tool for maintenance by understanding these patterns. Through our method, we reveal significant correlations between vibration patterns and pump condition, offering implications for extending pump lifespan and enhancing maintenance strategies in industries reliant on such machinery. Highlights: Centrifugal Pump Operation: Impeller rotation transfers fluid. Vibration Analysis Significance: Essential for predictive maintenance. Cavitation and Corrosion Effects: Trigger vibration, erode surfaces. Keywords: Centrifugal Pump, Corrosion, Vibration